Alcohol- and drug-related public violence in Europe. (November 2020) - van Amsterdam, Jan G.C.; Ramaekers, Johannes G.; Verkes, Robbert-Jan; Kuypers, Kim P.C.; Goudriaan, Anna E.; van den Brink, Wim
This study summarizes the literature about alcohol- and drug-related public violence in Europe. The proportion of all public violent incidents linked to alcohol was about 50 percent in the UK and ranged from 26 percent to 43 percent in Germany, Austria and the Netherlands. Public violence related to drugs is much lower (1.5–18.0 percent). Relatively many public violent incidents occur in relation to nightlife (80 percent of alcohol-related incidents). Though a considerable proportion of public violence was alcohol or drug related, the actual use of such substances was rarely ascertained in perpetrators' specimens. Such analysis is a prerequisite to heavier penalize alcohol- or drug-intoxicated perpetrators of public violence. More capacity should be deployed to measure alcohol and drugs in the specimens of violent perpetrators by analytical-chemical tests. As a result, more accurate estimates of substance-related public violence are obtained, which will serve policy makers and police enforcement officials to take measures for securing a safer public environment and sustainable nightlife industry in the future.